The anatomical relationship between the sural nerve and small saphenous vein: An ultrasound study of healthy participants. Issue 2 (13th December 2018) - Garagozlo, Cameron; Kadri, Omar; Atalla, Mina; Polanco, Fernando; Massaband, Andrew; Coey, James; Sulaiman, Sara
Abstract : Procedures involving the small saphenous vein (SSV) can result in sural nerve (SN) damage due to the proximity of the two structures. The relationship between the SN and SSV has previously been described in cadaveric studies with limited scope on surface landmarks. This study investigates the relationship between the SN and SSV in vivo through ultrasound. Transverse/short‐axis ultrasound scans of 128 legs (64 healthy participants) were taken by a single observer using a GE Logiq e ultrasound system with a 5–13 Hz linear transducer (GE Logiq 12L‐RS). The SN was identified and traced from the lateral malleolus to the popliteal fossa noting its course and proximity to the SSV. The distance between the SN and SSV was measured at points representing the distal 50% and 25% of the total leg length (the distance between the medial tibial condyle and the inferior edge of the medial malleolus). The SN and SSV were visualized in all participants regardless of BMI and atypical anatomical relationship were noted in 20.3%. The SN pierced the fascia in the distal 25.9% ± 5.3% of the total leg length. The distance between the SN and SSV was 4.06 ± 1.8 mm and 3.4 ± 1.4 mm in the distal 50% and 25% points of the total leg length, respectively. There was no significant effect of sex or body side. The SSV is a viable option for multiple vein harvest. Ultrasound visualization can be a beneficial tool for delineating variations of the SN in relation to SSV prior to surgery. Clin. Anat. 32:277–281, 2019. © 2018 Wiley Periodicals, Inc.